O direito à vida do Nascituro: em busca da efetividade do direito - Cazarotto, Caio de Souza (2017)
The present dissertation have to the principal objective to approach the complex theme for the unborn’s right of life in search of maximum effectiveness in the plan of brazilian legal framework. For this scope been reached, are brougth in the first place the different areas to the problem: the bioethics notion of the moment on which arise the individual human life and onwards when it has been its dignity recognized and guarded; the norms of brazilian legal sistem regarding directely to the theme; the critical analysis for the two jurisprudencial precedentes more recentes and importants that involve this topic; the presentation of a great historical panoramas of the 20th and 21st centuries about the relativization of the right of intrauterine human life for the influence of the specific agents, capable to interview into the brazilian legal-politic order. Finally, invoking of all these elements concurrently, search the proposition of roads and real juridics possibilities in order to that the brazilian legal framework can ensure more efficient of the unborn’s right of life, without neglecting the others fundamental rights closely linked with this, such as the pregnant’s dignity